Pesticide residues with hazard classifications relevant to non-target species including humans are omnipresent in the environment and farmer residences - Silva, Vera; Gai, Lingtong; Harkes, Paula; Tan, Gaowei; Ritsema, Coen J; Alcon, Francisco; Contreras, Josefa; Abrantes, Nelson; Campos, Isabel; Baldi, Isabelle; Bureau, Mathilde; Christ, Florian; et al. (Environment international, 2023)
Intensive and widespread use of pesticides raises serious environmental and human health concerns. The presence and levels of 209 pesticide residues (active substances and transformation products) in 625 environmental samples (201 soil, 193 crop, 20 outdoor air, 115 indoor dust, 58 surface water, and 38 sediment samples) have been studied. The samples were collected during the 2021 growing season, across 10 study sites, covering the main European crops, and conventional and organic farming systems. We profiled the pesticide residues found in the different matrices using existing hazard classifications towards non-target organisms and humans. Combining monitoring data and hazard information, we developed an indicator for the prioritization of pesticides, which can support policy decisions and sustainable pesticide use transitions. Eighty-six percent of the samples had at least one residue above the respective limit of detection. One hundred residues were found in soil, 112 in water, 99 in sediments, 78 in crops, 76 in outdoor air, and 197 in indoor dust. The number, levels, and profile of residues varied between farming systems. Our results show that non-approved compounds still represent a significant part of environmental cocktails and should be accounted for in monitoring programs and risk assessments. The hazard profiles analysis confirms the dominance of compounds of low-moderate hazard and underscores the high hazard of some approved compounds and recurring "no data available" situations. Overall, our results support the idea that risk should be assessed in a mixture context, taking environmentally relevant mixtures into consideration. We have uncovered uncertainties and data gaps that should be addressed, as well as the policy implications at the EU approval status level. Our newly introduced indicator can help identify research priority areas, and act as a reference for targeted scenarios set forth in the Farm to Fork pesticide reduction goals.
Keywords: Pesticides; Environmental Monitoring; Crops, Agricultural; pesticidy; Hazard; Dust; monitorování životního prostředí; voda; Distribution; zemědělské plodiny; SPRINT project; rezidua pesticidů; Farmers; Soil; zemědělci; lidé; Mixtures of pesticide residues; prach; Humans; Prioritization indicator; Pesticide Residues; půda; Water